GROWING AWARENESS OF ENVIRONMENTAL LOVE IN YOUTH: AN ACTION TOWARDS A PROSPEROUS VILLAGE IN LAMBAI VILLAGE, LAMBAI DISTRICT, NORTH KOLAKA DISTRICT - Ismail, Lukman; Mukramin, Sam’un; Muhammadong, Muhammadong (TOPLAMA, 2024)
Objective study This is to give information, service, education, grow awareness, and love the environment on teenagers: an action going to the village of Lambai, District Lambai, Regency North Kolaka. As for the method used, i.e., the method used in the study, this is PAR (Participatory Action Research). PAR is an approach that involves research involving all relevant parties in a way that is active in participatory study and ongoing action. The results of the study show that in running outreach programmes, the love environment for village prosperous in Village Lambai, District Subdistrict Wave faces a number of challenges in environment, economy, and cial. Because that is, the extension programmes that are designed with notice context cal Teenagers, as agents of change, need to be empowered to do so and play an important role in reaching objective development, prosperous villages, and sustainability. Recommended extension programmes cover strengthening the curriculum education environment, development of extracurricular programmes, empowerment of teenagers in taking decisions, training and workshops, use of social media, visiting programmes in the field, development of material education creative, partnership with the community, engagement programmes ilies, and mo, and monitoring and evaluation of sustainable.